Growth in stratospheric chlorine from short‐lived chemicals not controlled by the Montreal Protocol. Issue 11 (1st June 2015) - Hossaini, R.; Chipperfield, M. P.; Saiz‐Lopez, A.; Harrison, J. J.; von Glasow, R.; Sommariva, R.; Atlas, E.; Navarro, M.; Montzka, S. A.; Feng, W.; Dhomse, S.; Harth, C.; et al.
Abstract: We have developed a chemical mechanism describing the tropospheric degradation of chlorine containing very short‐lived substances (VSLS). The scheme was included in a global atmospheric model and used to quantify the stratospheric injection of chlorine from anthropogenic VSLS ( Cl y VSLS ) between 2005 and 2013. By constraining the model with surface measurements of chloroform (CHCl3 ), dichloromethane (CH2 Cl2 ), tetrachloroethene (C2 Cl4 ), trichloroethene (C2 HCl3 ), and 1, 2‐dichloroethane (CH2 ClCH2 Cl), we infer a 2013 Cl y VSLS mixing ratio of 123 parts per trillion (ppt). Stratospheric injection of source gases dominates this supply, accounting for ∼83% of the total. The remainder comes from VSLS‐derived organic products, phosgene (COCl2, 7%) and formyl chloride (CHClO, 2%), and also hydrogen chloride (HCl, 8%). Stratospheric Cl y VSLS increased by ∼52% between 2005 and 2013, with a mean growth rate of 3.7 ppt Cl/yr. This increase is due to recent and ongoing growth in anthropogenic CH2 Cl2 —the most abundant chlorinated VSLS not controlled by the Montreal Protocol. Key Points: Stratospheric Cl from short‐lived chemicals has increased significantly Increasing Cl due to rapid growth in surface emissions of CH2 Cl2 COCl2 and HCl from VSLS make a nonzero contribution to stratospheric Cl